Uso de anti-inflamatórios na exodontia de terceiros molares retidos : revisão sistemática e meta-análise - Berthold, Roger Correa de Barros (2018)
The surgical removal of impacted third molars is one of the most common procedures in oral surgery. The application of steroids or glucocorticoids in the perioperative period of these procedures is a practice used to reduce postoperative morbidity. However, the great variability of drugs and their applications makes it difficult to determine the true anti-inflammatory effect of these drugs. The present study evaluated the effect of corticosteroids on the reduction of postoperative pain, edema and trismus in the extraction of third molars by means of a systematic review and meta-analysis, comparing it with NSAIDs and control. A systematic search was performed on Pubmed, EMBASE and Cochrane Library databases, using specific terms assembled using customized strategies for each database. The results were transferred to Endnote x6 and analyzed by 2 independent reviewers, searching for relevant articles, by title and abstract. Seventy-five articles were retrieved in full text for analysis taking into consideration the eligibility criteria. After paired analysis, 34 articles met the criteria for final review. Considering the 100-mm visual analogue scale (VAS), the results indicated that individuals who received corticoids had a reduction in postoperative pain equivalent to -7.66 mm [-11.28, -4.04] at 48 h and -6.19 mm [-13.55, 1.18 ] at 168 h compared to the the control group. Considering the metric method for measuring the edema outcome, individuals who received corticoids showed a postoperative reduction of -2.52 mm [-3.27, -1.77] at 48 h and -0.56 mm [-0.79, -0.34] at 168 h compared to control. Considering the interincisal distance with respect to trismus, those who received corticoids had a postoperative reduction of -4.01 mm [-4.89, -3.12] at 48 h and -2.33 mm [-3.14, -1.51] at 168 h, compared to individuals in the control group. When corticoids were compared to NSAIDs and taking into consideration the standardized mean difference (SMD), the meta-analysis suggested a mild effect on reduction of pain and moderate effect on reduction of edema at 48 h postoperative: -0.26 [-0.45, -0.08] and -0.72 [-1.24, -0.20], respectively.